الأنماط القيادية و علاقتها بالأداء الوظيفي - معاش عيسى; هلوب حدة; عاجب بومدين (My University, 2023)
Through this research, the problematic of our research is addressed, which is the content of the relationship of leadership styles with the job performance of individuals in the organization. And we formulated a set of hypotheses in an attempt to answer the general and subsidiary problems, and we find that the general hypothesis revolves around that there is a relationship between leadership styles and the job performance of individuals, and this relationship is reflected in the influence of leadership styles (the democratic style, the autocratic style, the free leadership style) so that we find that An individual affected by the pattern applied to him, whether positively or negatively. And we assumed that there are factors affecting the leader and factors affecting the subordinates and other factors such as the environment. We assumed that the performance of individuals refers to the degree to which tasks are achieved and completed efficiently and effectively. At the end of the study, we tried to prove the validity of the hypotheses and deny other hypotheses. Keywords: leadership, leadership styles, job performance